2021
DOI: 10.1007/s00170-021-08149-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the fiber orientation on 3D C/C–SiC composite material and its formation mechanism of the machining surface

Abstract: Carbon/Carbon (C/C)-SiC composite materials attained much attention due to its unique properties like immense thermal conductivity, high corrosion, and abrasive resistance. Few scholars have systematically studied the grinding machinability of 3D C/C-SiC composite material. In this paper, the grinding experiment of 3D C/C-SiC composite material was carried out with a resin-bonded diamond grinding wheel. The effect of machining conditions on the grinding force, micromorphology, surface quality, and residual str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Figure10shows the residual stresses of the graphite, Si, and SiC phases on the worn surface of siliconized graphite rings under the applied loads of 500-1500 N with spindle speeds of 100-5000 rpm in 25 °C and 90 °C water, respectively. Residual compressive stress presents itself on the original surfaces of all the C, Si, and SiC phases, which is consistent with that by grinding[26]. The residual stress of C on the worn surface under all conditions is similar to that of the original with an average value of around −4 MPa.For the original siliconized graphite rings, Si has a residual stress of −33.1 MPa and SiC of −49.2 MPa.…”
supporting
confidence: 80%
“…Figure10shows the residual stresses of the graphite, Si, and SiC phases on the worn surface of siliconized graphite rings under the applied loads of 500-1500 N with spindle speeds of 100-5000 rpm in 25 °C and 90 °C water, respectively. Residual compressive stress presents itself on the original surfaces of all the C, Si, and SiC phases, which is consistent with that by grinding[26]. The residual stress of C on the worn surface under all conditions is similar to that of the original with an average value of around −4 MPa.For the original siliconized graphite rings, Si has a residual stress of −33.1 MPa and SiC of −49.2 MPa.…”
supporting
confidence: 80%
“…16,17 There are many factors affecting the properties of the C/C-SiC composite prepared by the RMI method, including the structure of the porous C/C preform, infiltration time, infiltration temperature, and so forth. 8,[18][19][20][21][22][23][24] For instance, the mechanical properties and microstructure of the C/C-SiC composite are largely affected by the structure of the porous C/C preform, including the woven structure of the carbon-fiber felt, the density of the C/C preform, the structure of pyrolytic carbon (PyC), and heat treatment (HT) state. In past research, Wang et al 8 studied the effect of bulk density of the C/C preform on the flexural strength of the C/C-SiC composite.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that abrasive wear and elastic deformation in the grinding process of silicon carbide are the main reasons why the actual machining depth is much lower than the preset machining depth of nano-scale. Li et al [18] studied the grinding machinability of 3D C/ C-sic composites, and conducted grinding experiments of 3D C/ C-sic composites with resin bonded diamond grinding wheel. The results showed that the main removal of C/ C-sic composites is considered as a brittle fracture mode.…”
Section: Introductionmentioning
confidence: 99%